Excessive dietary Cr6+ had no adverse effect on mud crab (Scylla paramamosain) but provoke consumers health risk - Yingying Zhang; Jiaxiang Luo; Tingting Zhu; Zheng Yang; Min Jin; Lefei Jiao; Qicun Zhou (Aquaculture Reports, 2022)
Hexavalent chromium (Cr6+) is a metallic contaminant that in organisms and poses a great threat to biological health and ecology due to its toxicity and biomagnification. However, the potential health risks to mud crabs and humans from dietary excessive Cr6+ were currently unknown. Therefore, a 9-week feeding trial was conducted to evaluate the toxic effects of dietary Cr6+ levels (1.4, 77.5 and 312.2 mg/kg) for mud crab (Scylla paramamosain). The results indicated that dietary Cr6+ levels had no significant effect on growth performance for mud crab. Cr concentrations in hepatopancreas and muscle significantly increased with dietary Cr6+ levels increasing from 1.4 to 312.2 mg/kg. The antioxidant capacity of mud crab was enhanced by increased the activities of superoxide dismutase (SOD) and scavenging capability for hydroxyl free radical (SCHR) to resist the Cr6+ toxicity. However, there was no statistical difference in the rate of apoptosis in hemocytes among all treatments. Expression levels of caspase 2 gene related to apoptosis in hemocytes significantly up-regulated with dietary Cr6+ level increasing from 1.4 to 312.2 mg/kg. For food safety, crabs fed diets with 77.5 and 312.2 mg/kg Cr6+ had target hazard quotient (THQ) values greater than 1 for the hepatopancreas, indicating a serious risk for human consumption. According to the target cancer risk (TCR) analysis, people who consumed muscle in mud crab fed diet with 312.2 mg/kg Cr6+ were at unacceptable cancer risk. Overall, the results of the present study indicated mud crab had a strong resistance to Cr6+ toxicity, and dietary excessive Cr6+ did not decline growth performance and survival, oxidative stress and apoptosis in mud crab. Excess Cr6+ were accumulated in tissues such as hepatopancreas and muscle, and consumption of crabs tissues fed diets with 77.5 and 312.2 mg/kg Cr6+ will provoke health and cancer risk in humans.